Blue grama and cactus - Burke, Indy, photographer (Colorado State University. Libraries, 1996)
Blue grama seedheads in mid range on SGS with OOF cow in backgrond and cactus in foreground.
Keywords: plants; SGS; Bogr; animals; cow; cactus